Adipocyte plasticity in tissue regeneration, repair, and disease. (October 2022) - Horsley, Valerie
Abstract : Mammalian tissue repair forms a scar that fills the injured area with a fibrotic lesion, limiting tissue function. Adipocytes, lipid-filled cells, well-known for energy storage and endocrine functions, can reside adjacent to or within many tissues, and are emerging as critical regulators of tissue repair. In this review, the plasticity and function of adipocytes to tissue repair and fibrosis in four tissues: skin, heart, skeletal muscle, and mammary gland, will be discussed. The dynamic nature of adipocytes as they release bioactive products, lipids, and adipokines, and their ability to form contractile fibroblasts, is emerging as an essential regulator of wound healing and tumorigenesis in multiple tissues. Thus, modulation of adipocytes may provide therapeutic avenues for regenerative medicine and cancer.